Catwings - Le Guin, Ursula K., 1929-; Schindler, S. D. (New York : Orchard Books, 1988)
Four young cats with wings leave the city slums in search of a safe place to live, finally meeting two children with kind hands.
5.4
3-6
Keywords: Cats -- Fiction; Fantasy; Fantasy fiction